THE IMPACT OF INNOVATION ON FIRM SUSTAINABLE COMPETITIVE ADVANTAGE IN SME FROM THE WEST REGION OF ROMANIA - Cristian-Dan BIRIȘ (Annals of the University of Oradea: Economic Science)
This study investigates the influence of product, service and process innovation on a company's competitive advantage. The study was conducted at small and medium-sized enterprises level from the Western Region of Romania. This research is structured in 5 parts: 1) an introduction illustrating the general context of the business environment in the Western Region of Romania and the opportunity to conduct this type of research; 2) a literature review illustrating the state of knowledge and other similar research conducted on this topic; 3) description of the methodological process of conducting empirical research by using the questionnaire as a method of collecting data from the regional business environment; 4) analysis and discussion based on empirical research following the aspects identified by applying the partial least squares structural equation modeling (PLS-SEM) method; 5) conclusions. This study comes to complement a series of previous studies both at national and international level, which aimed to research the impact of innovation on the competitiveness of SMEs. The results of the current research have highlighted the importance of process innovations, respectively product or service innovations, on obtaining sustainable competitive advantage by small and medium-sized enterprises in the Western Region of Romania, more precisely in Timiș, Arad, Hunedoara and Caraș-Severin counties. Moreover, the results of this study can be used both by general managers of companies, by entrepreneurs and last but not least by public policy makers with a direct